ANALISIS SPASIAL KERENTANAN BANJIR DI CIKARANG RAYA MENGGUNAKAN DATA SEKUNDER: STUDI KASUS 2015–2025 - Anang Suherman; Iwan Setiawan; Lili Somantri (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
SPATIAL ANALYSIS OF FLOOD VULNERABILITY IN CIKARANG RAYA USING SECONDARY DATA: CASE STUDY 2015–2025 Flooding remains a natural disaster that continues to pose a serious threat in the Cikarang Raya area, West Java. The region is under increasing pressure due to the conversion of land into built-up areas and drainage systems that are unable to accommodate the rising intensity of rainfall. This study aims to analyze spatial trends of flood vulnerability from 2015 to 2025 using secondary data. The data were obtained from various agencies, including flood-prone maps from the Regional Disaster Management Agency (BPBD) of Bekasi Regency, demographic data from the Central Bureau of Statistics (BPS) of Bekasi Regency, and land-use change information from the Geospatial Information Agency (BIG) and the Regional Development Planning Agency (Bappeda) of Bekasi Regency. The analysis was conducted descriptively and qualitatively, supported by Geographic Information System (GIS)-based visualization. The results indicate that Tambun Selatan, Cikarang Barat, and Cikarang Timur are the districts with the highest levels of flood vulnerability. The main contributing factors are rapid urbanization, the reduction of green open spaces, and the decline in water absorption capacity. Furthermore, the overlay of flood-prone maps from 2015 and 2025 reveals both shifts and expansions in the affected areas. These findings underscore the urgent need for disaster-mitigation-based spatial planning and the utilization of spatial data in decision-making processes. This research is expected to serve as an initial reference in formulating sustainable and adaptive development policies in response to environmental changes.